Relationship between organizational commitment and employee turnover - Hernández Chávez, Yazmín; Jaramillo Villanueva, José Luis; Hernández Chávez, Gerardo (Estudios de Administración, 2021)
The purpose of this paper is to analyze the relationship between organizational commitment and employee turnover by undertaking a cross-sectional quantitative albeit empirical study of small, medium and large firms of the apparel industry in the state of Tlaxcala, Mexico. The data were obtained using a structured questionnaire addressed to a stratified sample of workers at 85 small, 18 medium and 5 large companies. Based on a moderate significant correlation, the findings obtainedconfirm the relationship between organizational commitment and staff turnover. It may therefore be deduced that in order to reduce employee turnover, human talent managers should encourage the affective development of their employees. The limitations of this study are its sectorial character and its limitation to a specific territory.